Prevalence of dog erythrocyte antigens 1, 4, and 7 in galgos (Spanish Greyhounds). (July 2015) - Spada, Eva; Proverbio, Daniela; Viñals Flórez, Luis Miguel; del Rosario Perlado Chamizo, Maria; Perego, Roberta; Bagnagatti De Giorgi, Giada; Baggiani, Luciana
Galgos (Spanish Greyhounds), in common with other sighthounds, have higher hematocrits, hemoglobin concentrations, and red blood cell counts than other breeds. In addition to these hematological characteristics, the physical characteristics of these dogs (medium to large dogs with an easily accessible jugular vein and a good temperament) make galgos ideal blood donors. However, to date, there are only published reports concerning dog erythrocyte antigen (DEA) 1 in this breed. Information on DEAs 4 and 7 would be useful when recruiting blood donors to donation programs, as DEA 1 and 7–negative and DEA 4–positive dogs can be considered universal donors. Ethylenediamine tetra-acetic acid–anticoagulated jugular blood samples were collected from 205 galgos. Dogs were aged between 1 and 10 years, 102 were female (49.8%) and 103 male (50.2%), and all were living in South Madrid, Spain. All 205 blood samples were tested for DEA 1 by card agglutination, and 150 of these samples were tested for DEA 4 and DEA 7 by gel column agglutination using polyclonal anti-DEA antibodies. Of the 205 galgos blood samples typed, 112 out of 205 (54.6%) were positive for DEA 1. Of the 150 blood samples tested, all (150/150, 100%) were positive for DEA 4, and 12 out of 150 (8%) samples tested positive for DEA 7. Of these samples, 70 out of 150 (46.7%) were positive only for DEA 4. There was no relationship between blood types and sex. In addition to the hematological characteristics previously reported and the physical characteristics of these dogs, the relative prevalence of blood types DEA 1, 4, and 7 make galgos good candidates for blood donation in blood donor programs.